1989
DOI: 10.1017/s0305000900010679
|View full text |Cite
|
Sign up to set email alerts
|

A cross-language study of prosodic modifications in mothers' and fathers' speech to preverbal infants

Abstract: This study compares the prosodie modifications in mothers' and fathers' speech to preverbal infants in French, Italian, German, Japanese, British English, and American English. At every stage of data collection and analysis, standardized procedures were used to enhance the comparability across data sets that is essential for valid cross-language comparison of the prosodie features of parental speech. In each of the six language groups, five mothers and five fathers were recorded in semi-structured home observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
623
2
28

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 766 publications
(707 citation statements)
references
References 44 publications
36
623
2
28
Order By: Relevance
“…Results revealed that although IDS showed a significantly higher mean F 0 , maximum F 0 , and minimum F 0 for overall utterances, the F 0 range did not differ significantly between the two registers. These results replicate the findings in Fernald et al (1989); that is, mothers used a higher pitched voice when talking to infants than to adults, but did not alter their overall pitch range. Moreover, all averages were comparable to those reported in Fernald et al (1989), demonstrating that the lack of pitch range expansion in Fernald et al (1989) was not due to some idiosyncratic characteristics of their Japanese sample.…”
Section: Analysessupporting
confidence: 85%
See 4 more Smart Citations
“…Results revealed that although IDS showed a significantly higher mean F 0 , maximum F 0 , and minimum F 0 for overall utterances, the F 0 range did not differ significantly between the two registers. These results replicate the findings in Fernald et al (1989); that is, mothers used a higher pitched voice when talking to infants than to adults, but did not alter their overall pitch range. Moreover, all averages were comparable to those reported in Fernald et al (1989), demonstrating that the lack of pitch range expansion in Fernald et al (1989) was not due to some idiosyncratic characteristics of their Japanese sample.…”
Section: Analysessupporting
confidence: 85%
“…Specifically, caregivers are reported to use 'exaggerated' or 'sing-songy' intonation in IDS across many languages, and this intonation is often argued to be one of the universal properties of IDS (Ferguson 1977;Grieser and Kuhl 1988;Fernald et al 1989;Kitamura et al 2002). Interestingly, however, significant cross-linguistic differences are also known to exist in the characteristics of IDS (Bernstein Ratner and Pye 1984;Grieser and Kuhl 1988;Fernald et al 1989;Papoušek et al 1991;Kitamura et al 2002). Fernald et al (1989) compared intonational modifications in six languages/varieties (French, Italian, German, British English, American English, and Japanese), and found that all of them except Japanese showed pitch-range expansion in IDS.…”
Section: Data: Riken Japanese Mother-infant Conversation Corpusmentioning
confidence: 99%
See 3 more Smart Citations